La sangre que esconde el cuerpo: la subversión del deseo en el cine francés contemporáneo - Arnau Vilaró i Moncasí (Çédille: Revista de Estudios Franceses, 2017)
Since the beginning of this century French cinema has founded a unique universe in which, on one hand, new reports are showing an interest in sexuality and intimacy of the body and, on the other hand, the same bodies are willing to accept the sacrifice, rape or death in exchange for getting it wish. From the analysis of numerous films, the following article exposes that the tendency of new generations born in the transfer of a forged desire and realism that transcends into the fantastic. This transfer involves an investment of codes of French tradition while responding to the same reflection on the image that Nouvelle Vague conceived as travel and search for the Other.